System metabolic tools reveal fucoxanthin metabolism in Nitzschia laevis for the improvement of fucoxanthin productivity - Lu, Xue; Sun, Han; He, Yongjin; Yang, Shufang; Chen, Feng (Frontiers in Marine Science, 2023)
The production of fucoxanthin from microalgae is rapidly gaining popularity due to its exceptional productivity, lack of contamination, and straightforward extraction process. However, the optimal conditions for increasing biomass concentration and/or fucoxanthin content through the manipulation of light and carbon sources are context specific. This study explored fucoxanthin metabolism in Nitzschia laevis under heterotrophic and mixotrophic conditions using 13C tracer-based metabolic flux analysis, targeted metabolomics, and transcriptome analysis. Mixotrophic culture at 10 μmol m-2 s-1 improved fucoxanthin content by 27.54% but decreased biomass concentration by 15.65% compared to heterotrophic culture. At the molecular level, exposure to low light results in a reduction in carbon flux in the TCA cycle, leading to an increased flux toward carotenoid and fatty acid biosynthesis. The accumulation of high levels of citrate, isocitrate, and α-ketoglutaric acid is attributed to the reduced activity of the TCA cycle. Moreover, the metabolism of glyceraldehyde-3-phosphate and phosphoenolpyruvate was found to be more active under mixotrophic cultivation than heterotrophic ones, resulting in a substantial accumulation of fucoxanthin. The higher ATP and NADPH consumption provided sufficient energy for fucoxanthin and fatty acid biosynthesis. Furthermore, gene expression analysis revealed that low light upregulated the genes involved in fucoxanthin biosynthesis and promoted the violaxanthin cycle, especially after 12 h of cultivation. To improve fucoxanthin productivity, low light conditions were applied after a fed-batch culture, resulting in a 22.92% increase in fucoxanthin accumulation. The findings of this study offer valuable insights into the advantages of employing multi-stage cultivation techniques to improve microalgal production.